Introduction of a Fluorescent Probe to Amyloid‐β to Reveal Kinetic Insights into Its Interactions with Copper(II)1. (21st December 2014) - Branch, Thomas; Girvan, Paul; Barahona, Mauricio; Ying, Liming
Abstract The kinetics of the interactions between amyloid‐β (Aβ) and metal ions are crucial to understanding the physiological and pathological roles of Aβ in the normal brain and in Alzheimer's disease. Using the quenching of a fluorescent probe by Cu2+, the mechanism of Aβ/Cu2+ interactions in physiologically relevant conditions has been elucidated. Cu2+ binds to Aβ at a near diffusion‐limited rate, initially forming component I. The switching between component I and II occurs on the second timescale, with a significant energy barrier. Component I is much more reactive towards Cu2+ ligands and likely responsible for initial Aβ dimer formation. Clioquinol (CQ) is shown to sequester Cu2+ more effectively than other tested ligands. These findings have implications for the potential roles of Aβ in regulating neurotransmission, and for the screening of small molecules targeting Aβ–metal interactions.